AGENDA SETTING DENGAN PERPEKTIF KACAMATA PUBLIK - KHALAYAK MEDIA - Galih Geraldi Primayana (Jurnal Citra, 2022)
AbstractMass communication can be defined as communication through mass media, which at first only included print and electronic media and now the study of mass communication is becoming increasingly widespread and the process of mass communication is also in the spotlight of the public eye and media audiences for society, with the times the emergence of the agenda setting theory also gives influence to the community in controlling their environment and making agenda setting with the eyes of the public -media audience is very possible but for the effect or influence obtained depends on the personal of each individualKeywords: Media, Agenda setting, Public Viewpoint, Media Audience